Challenges and opportunities in education for refugees in Europe : from research to good practices - Dovigo, Fabio (Educational Research E-Books Online, Collection 2018, ISBN: 9789004375666., 2018)
"The wave of migrants arriving in Europe fleeing from war or hard living conditions represents both a challenge and a great educational opportunity for the European school systems. Currently, research and good practice in this field have been mainly developed within the boundaries of national educational politics and policies, addressing distinct populations. This fragmentation has stood in the way of a systematic analysis of the question at the European level, which is a necessary condition for the advancement of successful educational interventions. The book aims to offer substantive insights for researchers, policy makers, and teachers concerned with the effective inclusion of refugees within education by collecting and comparing the growing body of knowledge that is emerging from eight European countries."--